A New Method for Detection African Swine Fever Virus: Time-resolved Fluorescence Immunoassay - Chen, Cuicui (J Fluoresc, 2021)
African swine fever (ASF) has severely influenced the swine industry of the whole world. Fast and accurate African swine fever virus (ASFV) antigen detection is very important for ASF prevention. This study aims to establish a new detection method for detection ASFV antigen using time-resolved fluorescence immunoassay (TRFIA) in the nose and mouth discharge. A double antibody sandwich TRFIA method was optimized and established. Recombinant P30 recombinant antigen was captured by its antibodies immobilized on 96-well plate, and then banded together with another detection antibodies labeled with Europium(III) (Eu(3+)) chelates, finally time-resolved analyzer measured the fluorescence intensity. The performance of this TRFIA (sensitivity, specificity and accuracy) was evaluated using the clinical samples and compared with the nucleic acid testing method. The sensitivity of this TRFIA was 0.015 ng/mL (dynamic range 0.24–500 ng/mL) with high specificity. The recovery ranged from 92.00 to 103.62 %, the inter-assay CVs ranged from 5.50 to 11.96 %, and the intra-assay CVs was between 5.20 and 10.53 %. Additionally, the cutoff value was 0.016. TRFIA took only 45 min to generate results, and its detection capability comparable to the nucleic acid detection. This study developed a TRFIA method that could be used for qualitative/quantitative detection of ASFV antigen in pigs nasal discharge, which has high sensitivity, specificity and accuracy. This TRFIA provides a new method for rapidly screening ASFV infection in pigs industry.